Pengaruh Kualitas Pelayanan Jasa dan Kualitas Produk Terhadap Customer Satisfaction Pada Bayu Lagoon Resto Tebing Tinggi - Ira Hairani Br Damanik; Anggia Sari Lubis; Horia Siregar (Forum Kerjasama Pendidikan Tinggi, 2021)
The objective of the research was to determine the effect of service quality and product quality on customers’ satisfaction at Bayu Lagoon Resto Tebing Tinggi. The type of the research was quantitative descriptive research. The approach used was survey method. The poupulation of the researchwas the customer in Bayu Lagoon Resto Tebing Tinggi consisted of 900 consumers. The number of samples selected in thi research were 90 customers. The sampling technique used was simple random sampling. Data collection techniques were carried out by interview, questionnaire, observation, and the combination among them. Technique of analyzing the data was multiple linear regression analysis. The results of the study at a significant level of 5% indicate that (1) Service Quality of Service had a positive effect on Customer Satisfaction proved by tobserved 4.438 with a significant value of 0.000 lower than 0.05 (0.000 <0.05). (2) Product quality had a positive effect on Customer Satisfaction proved by t-observed of 5.080 with a significant value of 0.000 (0.000 <0.05). While, the determination test was 57.6%. Then the effect of differentiation in service quality and product quality on customer satisfaction was 57.6%, while the remaining 42.4% was affected by other variables unexamined in this research.